1997
DOI: 10.1021/ie9701480
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Ethylene in a Slurry Reactor Using a Nickel/Sulfated Alumina Catalyst

Abstract: During the oligomerization of ethylene over heterogeneous catalysts, the production of R-olefins may be lowered because of an accompanying deactivation of catalyst resulting from strong adsorption of products, by isomerization or by a tendency to copolymerize into branched products. The oligomerization of ethylene was studied using Ni(II)/sulfated alumina catalysts prepared with a nonporous fumed alumina (ALON) support. The influences of methods of catalyst preparation and activation upon oligomerization activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The microporous character of these materials leads to intracrystalline diffusion limitations which results in a rapid enrichment of polymeric waxes in the micropores. One of the approaches to overcome this problem was the use of catalysts with larger pores, such as Ni/sulfated-alumina [14] and Ni/amorphous silica-alumina [15]. More recently we have reported that Ni-exchanged Al-MCM-41 mesoporous materials revealed very interesting properties for ethylene oligomerization performed in a threephase batch reactor [8].…”
Section: Introductionmentioning
confidence: 99%
“…The microporous character of these materials leads to intracrystalline diffusion limitations which results in a rapid enrichment of polymeric waxes in the micropores. One of the approaches to overcome this problem was the use of catalysts with larger pores, such as Ni/sulfated-alumina [14] and Ni/amorphous silica-alumina [15]. More recently we have reported that Ni-exchanged Al-MCM-41 mesoporous materials revealed very interesting properties for ethylene oligomerization performed in a threephase batch reactor [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other usual homogeneous catalysts are AlR 3 (Ziegler type) and Me(OR) 4 -AlR 3 (Ziegler-Natta type) [1]. A significant research effort has also been directed to the development of a heterogeneous process to take advantage of easy separation of catalyst and oligomers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Nickel-loaded zeolites [2][3][4][5][6][7], usually obtained by metal ion exchange showed good catalytic activity in the gas-phase reaction of ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches to overcome these problems was the use of a catalyst with larger pores and tuneable acidity, under mild oligomerization conditions. It was reported that in a three-phase slurry reactor, at low temperature, the nickel/sulfated-alumina [9,10] and especially Ni-exchanged amorphous silica-alumina (NiSA) [11] catalysts are active and very stable for the ethylene oligomerization. Thus, the rate of ethylene oligomerization (120 • C, 3.5 MPa) obtained with NiSA (1.56 wt% Ni, 425 m 2 /g BET surface area) was 11.5 g/(g cat h).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, OLI investigations have been reported on the use of different Ni salts on various silica and alumina supports, 171 Ni/Al 2 O 3 and its phosphorus-promoted analogues, 172 NiSO 4 /TiO 2 -ZrO 2 173 and Ni/SO 2 À 4 /Al 2 O 3 . 174 Cai et al reported that NiSO 4 /Al 2 O 3 was active for OLI of propene; a propene conversion of 98% with 55-88% dimer selectivity could be obtained at 30 1C, 2.5 MPa and LHSV 2 h À1 . 175 In subsequent work on the dimerisation of ethene over NiSO 4 /Al 2 O 3 , it was reported that the nickel loading and temperature of calcination influenced the catalyst activity.…”
Section: Other Catalyst Typesmentioning
confidence: 99%